Self-collection of capillary blood using Tasso-SST devices for Anti-SARS-CoV-2 IgG antibody testing - Tess Hendelman; Anu Chaudhary; Angela LeClair; Kimberly van Leuven; Jacqueline Chee; Susan L. Fink; Emily J. Welch; Erwin Berthier; Brook A. Quist; Anna Wald; Mark H. Wener; Andrew N. Hoofnagle; et al. (2021)
Background Efforts to minimize COVID-19 exposure during the current SARS-CoV-2 pandemic have led to limitations in access to medical care and testing. The Tasso-SST kit includes all of the components necessary for remote, capillary blood self-collection. In this study, we sought to investigate the accuracy and reliability of the Tasso-SST device as a self-collection device for measurement of SARS-CoV-2 IgG antibodies. Methods Capillary blood was obtained via unsupervised and supervised application of the Tasso-SST device, and venous blood was collected by standard venipuncture. Unsupervised self-collected blood samples underwent either extreme summer or winter-simulated shipping conditions prior to testing. Sera obtained by all three methods were tested concurrently using the EuroImmun anti-SARS-CoV-2 S1 IgG assay in a CLIA-certified clinical laboratory. Results Successful Tasso-SST capillary blood collection by unsupervised and supervised administration was completed by 93.4% and 94.5% of participants, respectively. Sera from 56 participants, 55 with documented (PCR+) COVID-19, and 33 healthy controls were then tested for anti-SARS-CoV-2 IgG antibodies. Compared to venous blood results, Tasso-SST-collected (unstressed) and the summer- and winter-stressed blood samples demonstrated Deming regression slopes of 1.00 (95% CI: 0.99–1.02), 1.00 (95% CI: 0.98–1.01), and 0.99 (95% CI: 0.97–1.01), respectively, with an overall accuracy of 98.9%. Conclusions Capillary blood self-collection using the Tasso-SST device had a high success rate. Moreover, excellent concordance was found for anti-SARS-CoV-2 IgG results between Tasso-SST capillary and standard venous blood-derived sera. The Tasso-SST device should enable widespread collection of capillary blood for testing without medical supervision, facilitating epidemiologic studies.